1996
DOI: 10.1093/bja/77.4.496
|View full text |Cite
|
Sign up to set email alerts
|

Is recovery of neuromuscular transmission complete after the use of neostigmine to antagonize block produced by rocuronium, vecuronium, atracurium and pancuronium?

Abstract: To test if recovery of neuromuscular transmission is complete after the use of neostigmine under standardized conditions, we have measured adductor pollicis mechanical activity in response to 0.1 Hz (twitch height), train-of-four (TOF) and 100 Hz (RF 100 Hz) ulnar nerve stimulations. We studied 56 adult anaesthetized (thiopentone, fentanyl, nitrous oxide in oxygen) patients, allocated randomly to one of four groups (n = 14) to receive rocuronium (group Roc), vecuronium (group Vec), atracurium (group Atr) or pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
12
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 24 publications
2
12
0
1
Order By: Relevance
“…Measurements of T1 ⁄ control and train-of-four ratio (TOFR) were taken 3 min, 6 min, 9 min, 12 min and 15 min after the administration of neostigmine, and the values for the two groups were compared. It has been shown that 15 min after the administration of neostigmine at a T1 ⁄ control value of 0.25, TOFR often does not return to 0.9 [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Measurements of T1 ⁄ control and train-of-four ratio (TOFR) were taken 3 min, 6 min, 9 min, 12 min and 15 min after the administration of neostigmine, and the values for the two groups were compared. It has been shown that 15 min after the administration of neostigmine at a T1 ⁄ control value of 0.25, TOFR often does not return to 0.9 [14][15][16][17].…”
Section: Methodsmentioning
confidence: 99%
“…Further, it has been postulated that if neostigmine 40 lg.kg )1 is administered when T1 ⁄ control = 0.25, TOFR returns to a value of 0.9 after about 15 min [14][15][16]. For this reason, recovery from neuromuscular blockade was studied for 15 min after neostigmine administration in this study.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…Furthermore, cholinesterase inhibitors are unable to reverse deep neuromuscular blockade due to their mechanism of action. 35,36 In our patients, the pre-NMBA TOF ratio ranged from 0.45 to 1.0 and administration of the NMBA resulted in a maximal depth of neuromuscular blockade ranging from a TOF ratio of 0 to 0.19, or a PTC of 0 to 1. After reversal of neuromuscular blockade with sugammadex, all patients recovered from neuromuscular blockade to their preoperative TOF ratio, indicating that sugammadex reversal was complete and led to a rapid reappearance of normal muscle activity in our patients with myasthenia gravis.…”
Section: Reversal Of Neuromuscular Blockade With Sugammadex In Patienmentioning
confidence: 60%
“…Orta etkili kas gevşeticilerin kendi aralarında, kas gevşetici cinsi açısından, postoperatif rezidüel kürarizasyon insidansında fark olmadığını bildiren çalışmalar mevcuttur (16)(17)(18). Bunlardan Hayes ve ark.…”
Section: Discussionunclassified